Influência do exercicío físico em meio aquático no tecido muscular de ratos submetidos doença periodontal experimental - Brandão, Lidiane Ura Affonso (2016)
It’s possible to find some evidences that the odontogenic origined infections are related to muscle injuries development caused by exacerbated imunologic response, which can lead to miosin expression destruction and alterations. Furthermore, there are longitudinal and prospective studies evidences demonstrating that physically active adults have decresead risk of developing periodotitis. To date, no study has jointly explored the relationship of physical activity, by means of inflammatory biomarkers to periodontitis. The aim of the presente study was evaluate the muscle behaviour of rats submetd to inducedexperimenal periodontitis associated to water physical exercises. Twenty four Wistar male rats were divided in 4 groups: 1) control and sedentary (CS); 2) control and exercise (CE); 3) periodontal disease and sedentary (DPS); 4) periodontal disease and exercise (DPE). In periodontitis groups, the periodontal disease was induced by ligatures and the exercise ones did swimming activities and the rats submited to exercise did swmming activities for 4 weeks. Animals were euthanased at the 30 experimental day and fragments of gengival tissue and soleum muscle were colected and subjected to ELISA test and morphological and morphometric muscle analysis. Obtained data were analysed and evaluated using ANOVA and Tukey tests. Results demonstrated a higher TNF-α expression both in gengival as in muscle tissues of induced periodontitis rats, independently of physical activities (DPS and DPE), as a estatisticalty significant decrease in conjunctive tissue of periodontitis induced groups, associated or not to swimming exercise, it suggest that muscle injury propensity or a more difficult muscle regeneration in these groups. Thus, it was observed a relationship between periodontal disease and morphological muscle changes and, moreover, that water physical activity promoted a muscle regeneration acceleration.